P3_1 On the feasibility of neutrino sails - Peck, R. H.; Buttery, H. W.; Moore, C. D.Y.; Middleton, C. J. (Physics Special Topics, 2016)
In this paper we consider whether a neutrino sail, a sheet of material absorbing neutrinos and gaining thrust from their momentum change, is a viable method of spacecraft propulsion. We calculate the thrust that could be achieved per unit area and compare this to that possible using a photon solar sail. We also calculate the thickness of sail necessary assuming that there are no special conditions under which the cross section for neutrino interactions with nuclei can be increased. We find that a thickness of 34000 light years would be necessary if a sheet of osmium were used, whereas neutron star matter could achieve this at 189 km thickness. We conclude that a neutrino sail is not a practical method of propulsion.